Why Should We Care about Child Labor? The Education, Labor Market, and Health Consequences of Child Labor - Beegle, Kathleen; Dehejia, Rajeev; Gatti, Roberta (2012)
Despite the extensive literature on the determinants of child labor, the evidence on the consequences of child labor on outcomes such as education, labor, and health is limited. We evaluate the causal effect of child labor participation among children in school on these outcomes using panel data from Vietnam and an instrumental variables strategy. Five years subsequent to the child labor experience we find significant negative impacts on education, and also find a higher probability of wage work for those young adults who worked as children while attending school. We find few significant effects on health.